The Problem of Bias: An Epistemological Approach and Call for Ijtihad 15-17 Sha'ban 1412 / 19-21 February 1992 Cairo, Egypt (American Journal of Islam and Society, 1993)
The Intemational Institute of Islamic Thought (IIIT) is pleased tosponsor this important seminar, as its topic and objectives, the nature ofthe issues to be raised, and the points of view represented by thescholarly participants and their papers are of vital concern to the Islamicworld. Through its participation, the institute has opened a new chapterfor academic activity and intellectual jihad, particularly in Arabic and Islamiccultutal circles.As the institute joins the Union of Egyptian Engineers (UEE) in thispioneering intellectual effott, it seeks to articulate its third objective asregards the reform of the methodology of Islamic thought: the Islamizationof knowledge in order to build a new Islamic cultural order and leadthe ummah to the most beneficial ways of overcoming its backwardness.Moreover, as the IIIT joins the UEE in this undettaking, it seeks toexonerate itself from the charge that it is biased in favor of theoreticalthinking and thus insensitive to the applied sciences. While this is the impressionthat might be given by the institute's publications and statements,the truth is that these are indicative only of its priorities and havenothing to do with bias.Contemporary Western thought and cultute have begun to cast theirdatkness over everything in a way that obliterates, or neatly so, all non-Western thought and culture by weakening established concepts anddetracting from the importance of their soutces. The West has done thisunder the guise of academic objectivity, by endowing its own social sciencesand humanities with an assumed universality that makes of theirdubious disciplines not only a virtue, but the authoritative last word. Infact, however, the West's "universality" is little more that its own selfcentetednessand the stripping of others of all vestiges of their own civilizationand culture.The universality of Islam, however, is another matter entirely, for itincludes and integrates every people and every culture. Yet the West,more by means of its influence than its supposed universality, insists onpopularizing slogans like "knowledge for knowledge's sake" and "art forart's sake" in a less-than-subtle attempt to persuade others to renouncetheir own traditions, thought, and culture as a prelude to plunging headlonginto their supposedly universal counterparts in the West. Indeed, ...